Sanitary Hygiene and Analysis of Escherichia Coli Bacteria Content in Lalapan Kol at Pecel Lele Trader - Safitri, Anita; Novita, Lidya (PUI BiGME Universitas Jambi, 2021)
The presence of Eschericia coli (E.Coli) bacteria is one indicator of food contamination that can cause food-borne diseases. Fresh vegetables have nutritional advantages because they are consumed raw so that the nutrients contained in them are not denatured or changed. Types of vegetables that are usually consumed fresh have the potential to be detrimental to health because they are susceptible to microbial contamination. This study aims to review the sanitation hygiene of traders and determine the content of E.Coli bacteria in cabbage vegetables from fried catfish traders in one of the sub-districts in the city of Pekanbaru. The type of research used is survey and laboratory analysis. Technique sampling in this study is total sampling technique with a sample of 10 fried catfish traders. The results showed that hygiene and sanitation were still low in all traders. All traders do not use running water for washing vegetables and cutlery, and vegetables are not stored in closed containers. The results of bacterial analysis, it was found that 6 samples of fresh vegetables cabbage fried catfish contained E.Coli and the rest did not contain E.Coli bacteria. It can be concluded that the application of food sanitation hygiene by food handlers at several fried catfish traders in Pekanbaru City is in the poor category, because from 10 samples of cabbage vegetables, E.coli was found in 6 samples of cabbage vegetables.